Effects of Soy Protein and Calcium Levels on Mineral Bioaccessibility and Protein Digestibility from Enteral Formulas - Galan, Maria Gimena (2014)
Enteral formulas (EF) are complex food systems which have all the nutrients in their matrix for the complete human nourishment. However, there are components in EF which can interact with minerals, reducing their absorption, and thereof the EF nutritional quality. The effect of soy protein (SP) and Ca content on Fe, Zn, and Ca bioaccessibility and protein digestibility (%DP) was assessed using a response surface design in EF. Tested SP levels were 2.5?5.0 g/100 mL of total protein. Ca levels were adjusted with Ca citrate within a range between 50 and 100 mg/100 mL. SP content negatively influenced %DP and Fe, Zn and Ca bioaccessibility. As SP content increased, mineral bioaccessibility and %DP decreased, probably due to the increased levels of phytic acid and trypsin inhibitors from SP. Ca content only affected %DCa, which had a direct relationship with Ca levels, while did not affect Fe and Zn bioaccessibility or %DP. Since Ca citrate did not impair Fe and Zn bioaccessibility, it could be an appropriate Ca source for EF fortification